1995
DOI: 10.1111/j.1476-5381.1995.tb15011.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of nitric oxide in learning and memory and in monoamine metabolism in the rat brain

Abstract: 1 We investigated the effects of N0-nitro-L-arginine methyl ester (L-NAME), an inhibitor of nitric oxide (NO) synthase, on the performance of rats in a radial arm maze and in habituation tasks, and on monoamine metabolism in the brain. 2 Daily administration of L-NAME (10-60 mg kg-') resulted in a dose-dependent impairment of performance during the acquisition of the radial arm maze task, while it failed to affect performance in those rats that had previously acquired the task. 3 The rate of decrease in locomo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
54
1
3

Year Published

1998
1998
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 143 publications
(61 citation statements)
references
References 51 publications
(76 reference statements)
2
54
1
3
Order By: Relevance
“…It also leads to the degeneration of neurons in hippocampus which plays an important role in learning process (Guo et al 2010). A growing body of evidence suggests that reactive ROS play a crucial role in the development of these impairments as discussed above (Yamada et al 1995;Kucukatay et al 2007). The increased production of oxidants altered neurotransmitter release and increased membrane permeability (Gupta et al 1991).…”
Section: Resultsmentioning
confidence: 99%
“…It also leads to the degeneration of neurons in hippocampus which plays an important role in learning process (Guo et al 2010). A growing body of evidence suggests that reactive ROS play a crucial role in the development of these impairments as discussed above (Yamada et al 1995;Kucukatay et al 2007). The increased production of oxidants altered neurotransmitter release and increased membrane permeability (Gupta et al 1991).…”
Section: Resultsmentioning
confidence: 99%
“…This enzyme produces nitric oxide (NO), a molecule involved in neurosynaptic transmission, and is induced in many pathological conditions. Although the role of NO in learning and memory is still unclear, some studies have reported that systemic NO inhibition had deleterious effects in water maze learning (25)(26)(27). The role of iNOS in the hippocampus, therefore, may go beyond its well established detrimental function in neurological disorders and could contribute to the mechanisms underlying learning and memory.…”
Section: Discussionmentioning
confidence: 99%
“…These antagonists have also been found to protect against NMDAinduced neurotoxicity (Haberny et al, 1992;Dawson et al, 1993;Ayata et al, 1997). They also block NMDA-mediated convulsions (Nakamura et al, 1995), and impair learning and memory in several animal models (Ward et al, 1990;Chapman et al, 1992;BoÈ hme et al, 1993;HoÈ lscher & Rose, 1993;HoÈ lscher et al, 1995;Yamada et al, 1995;Harder et al, 1998;Ingram et al, 1998a,b;Meyer et al, 1998;Zou et al, 1998). However, there is also evidence that inhibition of NOS does not impair learning or prevent the induction of long-term potentiation and NMDA-induced convulsions in animals (Buisson et al, 1993;Bannerman et al, 1994a,b).…”
Section: Discussionmentioning
confidence: 99%